An assessment of ecological values and conservation gaps in protection beyond the corridor of the Appalachian Trail. Issue 6 (3rd May 2019) - McKinley, Peter S.; Belote, R. Travis; Aplet, Gregory H.
Abstract: The Appalachian Trail (AT) traverses the Appalachian Mountains across 11 degrees of latitude from Springer Mountain in Georgia to Maine's Mt. Katahdin. The 3, 524 km (2, 190‐mile) long trail is buffered within a conserved corridor that is at least 305 m wide and covers approximately 101, 000 hectacres (250, 000 acres) overseen by the National Park Service (NPS), making it one of the largest NPS units in the East. Although a continuous marked trail has been established since 1937, protection of the corridor was not complete until the last couple of decades. Additional conservation designations exist adjacent to much of the trail corridor, but significant gaps in protection remain. A variety of land trusts and other nonprofit conservation organizations, federal and state land management agencies, and regional trail clubs overseen by the Appalachian Trail Conservancy (ATC) actively seek to add to the local, regional, and national conservation significance of this landscape or to improve the management of lands already protected. Here, we assess biodiversity and ecological integrity along the entire AT among 2, 123 trail sampling segments and four planning regions. We evaluated gradients of biodiversity and ecological integrity in relation to the existing management status of trail sampling segments to identify gaps in protection of high value areas. The AT possesses high species diversity at the southern end, where much of it exists in federal multiple‐use management, and high ecological integrity in the north on private timberlands. Inadequately protected areas of such high biological diversity and ecological integrity occur throughout the trail. Our data are analyzed at the scale of the entire AT with summaries and comparisons among broad sections, regions, states, and some specific locations. We include our spatial data so that it may be used for analyses and prioritization at multiple scales from the local maintenance club to the ATC.